The Senescence-Associated Secretory Phenotype (SASP) in the Challenging Future of Cancer Therapy and Age-Related Diseases - Lorenzo Cuollo; Fabrizio Antonangeli; Angela Santoni; Alessandra Soriani (Biology, 2020)
Cellular senescence represents a robust tumor-protecting mechanism that halts the proliferation of stressed or premalignant cells. However, this state of stable proliferative arrest is accompanied by the Senescence-Associated Secretory Phenotype (SASP), which entails the copious secretion of proinflammatory signals in the tissue microenvironment and contributes to age-related conditions, including, paradoxically, cancer. Novel therapeutic strategies aim at eliminating senescent cells with the use of senolytics or abolishing the SASP without killing the senescent cell with the use of the so-called “senomorphics”. In addition, recent works demonstrate the possibility of modifying the composition of the secretome by genetic or pharmacological intervention. The purpose is not to renounce the potent immunostimulatory nature of SASP, but rather learning to modulate it for combating cancer and other age-related diseases. This review describes the main molecular mechanisms regulating the SASP and reports the evidence of the feasibility of abrogating or modulating the SASP, discussing the possible implications of both strategies.